Flexible ZIFs: Probing guest‐induced flexibility with CO2, N2 and Ar adsorption - Noguera Díaz, Antonio (2019)
BACKGROUND: The effect of framework topology on the guest-induced flexibility of several crystalline zeolitic imidazolateframeworks (ZIF-7, ZIF-9, ZIF-11 and ZIF-12) was investigated via analysis of experimental nitrogen (N2), carbon dioxide (CO2)and argon (Ar) isotherms at 77 K (N2 and Ar) and 273 K (CO2) for gas pressures up to 0.13MPa. RESULTS: The experimental isotherms of these frameworkswere analysed in order to investigate their structural flexibility usinggases with kinetic diameters equal to or larger than the diameters of their static pore apertures. The results of gas sorptionmeasurements indicate guest-induced phase changes for ZIF-7 and ZIF-9 (SOD topologies). ZIF-12 (RHO topology) also showsuptake for gases, despite its pore-limiting diameter being smaller than the kinetic diameters of the adsorbed molecules. CONCLUSIONS: This work highlights the ability of ZIFs with different framework topologies to change their structureandincrease their pore apertureuponinteraction with certain gases.These findings are key in thedevelopment ofmore selectiveZIF-basedmaterials for important industrial applications including low-energy gas separations, catalytic nanoreactors and sensortechnology.